Lasing Operation under Long‐Pulse Excitation in Solution‐Processed Organic Gain Medium: Toward CW Lasing in Organic Semiconductors. Issue 21 (9th September 2020) - Mai, Van T. N.; Shukla, Atul; Senevirathne, A. M. Chathuranganie; Allison, Ilene; Lim, Hyunsoo; Lepage, Romain J.; McGregor, Sarah K. M.; Wood, Michael; Matsushima, Toshinori; Moore, Evan G.; Krenske, Elizabeth H.; Sandanayaka, Atula S. D.; et al.
Abstract: High mechanical flexibility and wavelength tunability of organic semiconductor materials have propelled the development of organic semiconductor lasers (OSLs) as a complementary technology to current inorganic lasers. While excellent progress has been made across multiple aspects of OSLs, demonstration of long‐pulse operation [quasi‐continuous wave (qCW) or continuous wave (CW)] lasing has presented significant challenges due to the detrimental accumulation of triplets under long‐pulse photoexcitation and substantial quenching of singlet excitons, arising from singlet‐triplet annihilation (STA). In particular, qCW or CW lasing from solution‐processed OSL materials has not been reported, and thus remains a long‐thought objective in optoelectronic research. Using a novel bis( N ‐carbazolylstyryl)‐9, 9‐dihexylfluorene (BSFCz ), the first solution‐processable organic laser dye demonstrating lasing oscillation in the long‐pulse photoexcitation regime (up to 10 ms pulse width) with a low threshold (420 W cm −2 ), which in part can be attributed to its negligible spectral overlap between triplet excited‐state absorption and laser emission, is herein reported. Temporal emission profiles below and above the lasing threshold also demonstrate that STA has a negligible effect on emission. These combined observations show BSFCz incur low losses due to triplet excited‐states, leading to extremely small changes in lasing thresholds when moving from pulsed to qCW (>1 ms) excitation. Abstract : The first lasing activity under long‐pulse (up to 10 ms) photoexcitation from a new solution‐processable organic semiconductor laser dye is demonstrated. Its negligible spectral overlap between triplet excited‐state absorption and emission, coupled with its high molar extinction coefficient, high radiative decay rate, short excited‐state lifetimes, and low solid‐state ASE and lasing thresholds (0.9–1.1 µJ cm −2 ), enables the long‐pulse lasing.